Phacomatosis pigmentovascularis type IIa - case report - Majoriê Mergen Segatto; Eloísa Unfer Schmitt; Laura Netto Hagemann; Roberta Castilhos da Silva; Cristiane Almeida Soares Cattani (Sociedade Brasileira de Dermatologia, 2013)
Phacomatosis Pigmentovascularis is a rare syndrome characterized by capillary malformation and pigmentary nevus. A case of a 2-year-old patient is reported, who presented extensive nevus flammeus and an aberrant Mongolian spot, without systemic disease, manifestations that allow us to classify this case as type IIa Phacomatosis Pigmentovascularis, according to Hasegawa's classification.